New tandem Ugi/intramolecular Diels–Alder reaction based on vinylfuran and 1,3-butadienylfuran derivatives - Horak, Yuriy I.; Lytvyn, Roman Z.; Vakhula, Andrii R.; Homza, Yuriy V.; Pokhodylo, Nazariy T.; Obushak, Mykola D. (Beilstein Journal of Organic Chemistry, 2025)
A new tandem sequence involving the Ugi reaction and Diels–Alder [4 + 2] cycloaddition based on vinylfuran and 1,3-butadienylfuran derivatives was designed and studied. It was found that in the case of 3-(furan-2-yl)acrylaldehyde, a one-pot Ugi reaction and intramolecular Diels–Alder vinylarene (IMDAV) reaction leads to the formation of the insufficiently studied furo[2,3-f]isoindole derivatives. Ugi adducts formed from (E)-3-(furan-2-yl)acrylaldehyde, maleic acid monoanilide, isonitrile, and an amine spontaneously underwent the IMDAV reaction with a high level of stereoselectivity, leading to single pairs of enantiomers of 4,4a,5,6,7,7a-hexahydro-3aH-furo[2,3-f]isoindole core in excellent yields. Under the same conditions, the (2E,4E)-5-(furan-2-yl)penta-2,4-dienal gives an Ugi adduct that undergoes the IMDA reaction without involving the furan core. The cycloaddition leads to the formation of 2,3,3a,4,5,7a-hexahydro-1H-isoindoles in high yields. The studied tandem Ugi and intramolecular Diels–Alder reactions allow high substituent variation in the named isoindoles.
Keywords: 1,3-butadienylfuran; furo[2,3-f]isoindole; intramolecular Diels–Alder reaction; isoindole; one-pot; Ugi reaction; vinylfuran